Pengaruh Durasi Terhadap Retensi Audiens Dalam Motion Graphic Wajib Pajak Non Efektif - Muhammad Farhan Alkautsar; Muhammad Sukriyatma; Daffa Akmal Aminuddin; Amata Fami (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to see the effect of motion graphic duration on audience retention levels when conveying information about non-effective taxpayers and also to make recommendations for optimal duration to increase audience retention by using non-effective taxpayer motion graphics as a case study. A quantitative approach with a correlational type was used in conducting this research, as well as the use of YouTube Analytics to analyze data on audience retention levels while watching motion graphics. This research found a significant linear relationship between the duration of motion graphics and audience retention based on the motion graphics presented. A duration that exceeds three minutes can decrease audience retention.